Reconstructing Teacher Authority and Student Motivation: A Critical Discourse Analysis of Student Resistance Among Generation Z in Great Teacher Onizuka - Rukandana, Cucu; Fauzan, Akbar; Dormido, Yasmin Pascual (Indonesian Journal of Education and Mathematical Science, 2025)
This research explores student resistance, teacher authority, and motivation growth among Generation Z learners through Van Dijk’s critical discourse analysis in the Japanese series Great Teacher Onizuka (GTO). Using a qualitative descriptive method, this study analyzes selected scenes from episodes 1 to 8, supported by relevant literature and online sources. Data were collected through observation, reading, and note-taking, and analyzed using data reduction, display, and conclusion techniques. The findings show that: (1) The text structure includes macrostructure elements such as themes of resistance and transformation, superstructure through the narrative plot, and microstructure in semantic (meaning, details), syntactic (sentence forms), and stylistic (tone, diction) aspects. (2) Social cognition reflects how both students and teachers construct meaning and interpret authority, empathy, and discipline. (3) Social context highlights how Generation Z’s educational values and behaviors, shaped by digital culture and a desire for autonomy, challenge traditional schooling systems. The series illustrates how emotional intelligence and alternative teaching approaches can help bridge generational gaps and reconstruct authority in a more humane and effective manner.